Posterior cingulate cortex targeted real‐time fMRI neurofeedback recalibrates functional connectivity with the amygdala, posterior insula, and default‐mode network in PTSD. Issue 3 (15th February 2023) - Lieberman, Jonathan M.; Rabellino, Daniela; Densmore, Maria; Frewen, Paul A.; Steyrl, David; Scharnowski, Frank; Théberge, Jean; Neufeld, Richard W. J.; Schmahl, Christian; Jetly, Rakesh; Narikuzhy, Sandhya; Lanius, Ruth A.; et al.
Abstract: Background: Alterations within large‐scale brain networks—namely, the default mode (DMN) and salience networks (SN)—are present among individuals with posttraumatic stress disorder (PTSD). Previous real‐time functional magnetic resonance imaging (fMRI) and electroencephalography neurofeedback studies suggest that regulating posterior cingulate cortex (PCC; the primary hub of the posterior DMN) activity may reduce PTSD symptoms and recalibrate altered network dynamics. However, PCC connectivity to the DMN and SN during PCC‐targeted fMRI neurofeedback remains unexamined and may help to elucidate neurophysiological mechanisms through which these symptom improvements may occur. Methods: Using a trauma/emotion provocation paradigm, we investigated psychophysiological interactions over a single session of neurofeedback among PTSD ( n = 14) and healthy control ( n = 15) participants. We compared PCC functional connectivity between regulate (in which participants downregulated PCC activity) and view (in which participants did not exert regulatory control) conditions across the whole‐brain as well as in a priori specified regions‐of‐interest. Results: During regulate as compared to view conditions, only the PTSD group showed significant PCC connectivity with anterior DMN (dmPFC, vmPFC) and SN (posterior insula) regions, whereas both groups displayed PCC connectivity with other posterior DMN areas (precuneus/cuneus). Additionally, as compared with controls, the PTSD group showed significantly greater PCC connectivity with the SN (amygdala) during regulate as compared to view conditions. Moreover, linear regression analyses revealed that during regulate as compared to view conditions, PCC connectivity to DMN and SN regions was positively correlated to psychiatric symptoms across all participants. Conclusion: In summary, observations of PCC connectivity to the DMN and SN provide emerging evidence of neural mechanisms underlying PCC‐targeted fMRI neurofeedback among individuals with PTSD. This supports the use of PCC‐targeted neurofeedback as a means by which to recalibrate PTSD‐associated alterations in neural connectivity within the DMN and SN, which together, may help to facilitate improved emotion regulation abilities in PTSD.